2014
DOI: 10.1155/2014/674179
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Considerations of the Suprascapular Nerve in Rotator Cuff Repairs

Abstract: Introduction. When using the double interval slide technique for arthroscopic repair of chronic large or massive rotator cuff tears, the posterior interval release is directed toward the scapular spine until the fat pad that protects the suprascapular nerve is reached. Injury to the suprascapular nerve can occur due to the nerve's proximity to the operative field. This study aimed to identify safe margins for avoiding injury to the suprascapular nerve. Materials and Methods. For 20 shoulders in ten cadavers, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, it is necessary to avoid the risk of neurovascular injury during deposit stress and perforation in the supraspinatus muscle. The suprascapular nerve courses through the suprascapular notch an average of 3.42 cm from the superior end of the glenoid fossa 9 . Another risk with this technique is damage to the supraspinatus muscle during withdrawal of the calcium deposit.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to avoid the risk of neurovascular injury during deposit stress and perforation in the supraspinatus muscle. The suprascapular nerve courses through the suprascapular notch an average of 3.42 cm from the superior end of the glenoid fossa 9 . Another risk with this technique is damage to the supraspinatus muscle during withdrawal of the calcium deposit.…”
Section: Discussionmentioning
confidence: 99%
“…Two glenoid anchors can be enough, although if the graft is >35 mm in the anterior-posterior dimension or the distance between the 2 glenoid anchors is >20 mm, a third anchor can be placed in the glenoid without increasing the risk of suprascapular nerve injury. 16,17 Since the original technique of Mihata et al 3 using a fascia lata, different grafts have been described for SCR. Dermal allograft has gained popularity for theitheoretical advantage of reducing donor site morbidity, shorter operative times, and easy preparation, although no clinical studies have confirmed the equivalence of the 2 grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Two glenoid anchors can be enough, although if the graft is >35 mm in the anterior-posterior dimension or the distance between the 2 glenoid anchors is >20 mm, a third anchor can be placed in the glenoid without increasing the risk of suprascapular nerve injury. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…The SSN lies at the suprascapular groove. The surgeon 4), supraspinatus muscle (5), superior angle of the scapula (6), levator scapulae muscle (7), trapezius muscle (sectioned) (8), and serratus anterior muscle ( 9) with insertions at the ribs. e470 must be aware of the shape of the notch, as well as the location of the suprascapular artery, which may vary.…”
Section: Surgical Techniquementioning
confidence: 99%
“…With 3 cm of retraction of the SSP, the motor branch of the SSN was stretched. [6][7][8][9][10] The real incidence of this situation is undetermined, but it has been reported to be present in 8% to 27% of massive rotator cuff tears. [11][12][13] The reduction of the tendon to the original footprint during cuff repair may be advantageous to nerve function and lead to improvements in postoperative pain and strength.…”
mentioning
confidence: 99%